5Gbps HG 0,1 and HG 0,3 optical mode division multiplexing for RoFSO - Amphawan, Angela; Chaudhary, Sushank; Din, Roshidi; Omar, Mohd Nizam (2015)
Radio-over-free-space optics (Ro-FSO) technology harnesses the large capacity of optical fiber and the mobility native to wireless networks.To increase the capacity of Ro-FSO networks, this work introduces a new optical mode division multiplexing (MDM) scheme for Ro-FSO by incorporating optical Hermite-Gaussian modes HG 0, 1 and HG 0, 3 for transmitting two distinct 2.5 Gbps data modulated on 10 GHz radio subcarriers.Signal-to-noise ratios and biterror-rates show successful 2 × 2.5Gbps data transmission of 10GHz radio-modulated subcarriers over the two HG optical carriers through a 800m free-space channel.